2019
DOI: 10.3390/vaccines7010019
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response Following Infection of Mouse CNS with Virulent and Attenuated Vaccinia Virus Strains

Abstract: Viral infections of the central nervous system (CNS) lead to a broad range of pathologies. CNS infections with Orthopox viruses have been mainly documented as an adverse reaction to smallpox vaccination with vaccinia virus. To date, there is insufficient data regarding the mechanisms underlying pathological viral replication or viral clearance. Therefore, informed risk assessment of vaccine adverse reactions or outcome prediction is limited. This work applied a model of viral infection of the CNS, comparing ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The quantitative PCR (qPCR) primers and probes used for the detection of PR8 were PR8-PA-FW: CGGTCCAAATTCCTGCTGA; PR8-PA-RW: CATTGGGTTCCTTCCATCCA; and PR8-PA-Probe: CCAAGTCATGAAGGAGAGGGAATACCGCT. Total RNA extracted from the lungs of mice infected with IAV or SARS-CoV-2 or coinfected at 2 dpSi and 4 dpIi was used to measure the differential expression of genes by qRT-PCR using corresponding specific primers printed on 96-well plates (Custom TaqMan Array Plates, Applied Biosystems TM ) as previously described 28 . Briefly, 1 µg of cDNA was synthesized from RNA using a Verso cDNA Synthesis Kit (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's instructions.…”
Section: Cells Vero E6 Cells (Atcc® Crl-1586tm) and Madin-darby Canine Kidney (Mdck) Cells (Atcc® Ccl-34™mentioning
confidence: 99%
“…The quantitative PCR (qPCR) primers and probes used for the detection of PR8 were PR8-PA-FW: CGGTCCAAATTCCTGCTGA; PR8-PA-RW: CATTGGGTTCCTTCCATCCA; and PR8-PA-Probe: CCAAGTCATGAAGGAGAGGGAATACCGCT. Total RNA extracted from the lungs of mice infected with IAV or SARS-CoV-2 or coinfected at 2 dpSi and 4 dpIi was used to measure the differential expression of genes by qRT-PCR using corresponding specific primers printed on 96-well plates (Custom TaqMan Array Plates, Applied Biosystems TM ) as previously described 28 . Briefly, 1 µg of cDNA was synthesized from RNA using a Verso cDNA Synthesis Kit (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's instructions.…”
Section: Cells Vero E6 Cells (Atcc® Crl-1586tm) and Madin-darby Canine Kidney (Mdck) Cells (Atcc® Ccl-34™mentioning
confidence: 99%
“…A GLP toxicology study performed by a third-party company to determine the safety and biodistribution of CF33-hNIS-anti-PD-L1 in tumor bearing C57BL/6 mice treated with single or multiple injections of the virus at various dose levels showed no virus-related toxicity. Furthermore, intracranial injection of the virus at a dose 10 times higher than the lethal dose of WR strain 14 , 15 in C57Bl/6 mice did not show clinically meaningful virus-related toxicities. Finally, the risk for horizontal transmission of the virus using an experimental setup to mimic the clinical scenario suggested that the risk for horizontal transmission for this virus is minimal.…”
Section: Discussionmentioning
confidence: 91%
“…Wild-type vaccinia virus such as the WR strain has been shown to cause severe neurotoxicity in mice at a dose as low as 100 PFU 14 , 15 when injected intracranially. In order to rule out the possibility of a neurotoxic effect of CF33-hNIS-anti-PD-L1, we used CF33-hNIS-anti-PD-L1 virus at a dose 10 times higher (1,000 PFU) than the dose reported to cause severe neurotoxicity for wild-type vaccinia virus.…”
Section: Resultsmentioning
confidence: 99%
“…were harvested and stored in -80°C until further processing. Organs were processed for titration in 1.5 mL of ice-cold PBS as previously described 15 . Part of the processed tissue samples was used immediately for RNA extraction for IAV viral RNA determination and for gene expression, while the other part was kept in -80°C until further processing for viral titration (used for SARS-CoV-2 pfu).…”
Section: Determination Of Viral Load In Organsmentioning
confidence: 99%
“…The PFU Equivalent per organ (pfuE/organ) were calculated from standard curve generated from virus stocks. qPCR primers and probes for the detection of PR8: PR8-PA-FW: Total RNA extracted from lungs of mice infected with IAV or SARS-CoV-2, or coinfected, at 2 dpSi and 4 dpIi was used to measure differently-expressed genes by qRT-PCR using the corresponding specific primers printed on 96 well plates (Custom TaqMan Array Plates, Applied BiosystemsTM) as previously described 15 . Briefly, 1 microgram cDNA was synthesized out of the RNA using Verso cDNA Synthesis Kit (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's instructions.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%